Grammatical Issues in Judicial Interpretation – Does Legal Practice Needs Linguistic Theory? Based on Polish Courts’ Decisions - Zeifert Mateusz (Comparative Legilinguistics, 2018)
Most interpretational problems in law pertain to the meaning of words. However, in this paper I address problems caused in Polish courts by grammar (namely: syntax and inflexion) of legal provisions. One can distinguish five main sources of grammatical issues in judicial interpretation of law: syntax of a sentence (i.e. order of words), conjunctive words (i.e. i, lub), punctuation marks (i.e. comma, semicolon, dash), nominal grammatical categories (i.e. number, gender), verbal grammatical categories (i. e. aspect, tense, mood). Traditional Polish canons of interpretation offer no clues on how to deal with such issues, stating only that statutes should be construed in accordance with the rules of grammar. In fact, cases in which such interpretational issues occur, are decided in a highly incoherent manner. The courts tend to feel a tension between grammatical form of a provision and its purpose, function, or other extra-linguistic values. I think the main reason of such controversy is a very limited vision of grammar shared by the courts, stemmed from primary school rather than contemporary linguistic theories.